Histidine-Rich Glycoprotein Modulates the Anticoagulant Activity of Heparin in Human Plasma - Lijnen, H R; Van Hoef, B; Collen, D (Thrombosis and Haemostasis, 1984)
Addition of 0.05 IU of heparin per ml normal plasma prolongs its thrombin time from 20 to 27s, but that of plasma specifically depleted in histidine-rich glycoprotein (by immunoadsorption) from 20 to 180s. Reconstitution of the depleted plasma with normal plasma or with purified histidine-rich glycoprotein normalizes its thrombin time.In 54 plasma samples from hospitalized patients a significant negative correlation was found between the anticoagulant activity of heparin measured by thrombin inhibition and the plasma level of histidine-rich glycoprotein (r = 0.69). It is concluded that the level of histidine-rich glycoprotein modulates the anticoagulant activity of heparin in human plasma to an extent which appears to be pharmacologically and possibly clinically relevant.
Keywords: Histidine-rich glycoprotein; Heparin; Anticoagulant activity